The collective mode spectrum in polar phase of superfluid ³He - Brusov, P.N.; Lomakov, M.N.; Brusova, N.P. (Физика низких температур, 1995)
Using the path integration technique, developed by Brusov and Popov earlier [1], we calculate the collective mode spectrum at zero momentum of excitations for polar phase of superfluid ³He. We found six modes with energy E = (1.20 - 1.75i)△₀ which damp strongly and three Goldslone modes with zero energy at zero momentum of excitations.